The Effects Of The W-Beam Guardrail On Soft Body Upon Impact - Aini Zuhra Abd. Kadir; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal 482167 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2008)
Includes bibliographical references and index.